Revision of the genus Fascaplysinopsis, the type species Fascaplysinopsis reticulata (Hentschel, 1912) (Porifera, Dictyoceratida, Thorectidae) and descriptions of two new genera and seven new species - Ekins, Merrick; Erpenbeck, Dirk; Debitus, Cécile; Petek, Sylvain; Mai, Tepoerau; Wörheide, Gert; Hooper, John N.a. (Zootaxa, 2023)
The present study examines the taxonomy of sponge specimens with unique chemistry collectively known as Fascaplysinopsis reticulata (Hentschel, 1912). Examination of Hentschel’s original species upon which the genus Fascaplysinopsis Bergquist, 1980 was based in conjunction with a comparison with recent Indo-west Pacific collections, using morphological and molecular analyses (ITS and 28S rDNA), revealed extensive variation. Fascaplysinopsis reticulata was found to be a species complex comprising the genus Fascaplysinopsis, as well as two new genera: Skolosachlys gen. nov. and Rubrafasciculus gen. nov. The new species of Fascaplysinopsis described are F. palauensis sp. nov., F. klobos sp. nov. and F. ronquinni sp. nov. The new species of Skolosachlys gen. nov. described herein are: S. enlutea sp. nov. and S. nidus sp. nov. The new species described of Rubrafasciculus gen. nov. includes: R. cerasus sp. nov. and R. fijiensis sp. nov..